Study of evaluation of hepatoprotective potential of lycopene in rat models of paracetamol and antitubercular drugs (isoniazid + rifampicin) induced hepatotoxicity - Joshi, Shirish Shashikant; Tadavi, Firoz Mubarak; T. A., Manjunatha; Kurle, Dnyaneshwar Gurunath (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The exact role of lycopene has not been studied in the past for its hepatoprotective effects. Hence it was decided to explore its anti-oxidant and anti-inflammatory properties in acute and chronic models of drug- induced hepatotoxicity with the aim to evaluate hepatoprotective potential in rat models of paracetamol and antitubercular drugs (isoniazid + rifampicin) induced hepatotoxicity. Methods: The study was carried out in 70 Wistar rats in two phases. In phase I, models of paracetamol and anti-tubercular drugs induced hepatotoxicity were standardized in 22 Wistar rats and in phase II, hepatoprotective potential of lycopene was evaluated in paracetamol and anti-tubercular drugs induced hepatic damage using 48 Wistar rats. The effects of lycopene were compared with silymarin. Results: There was a significant (p <0.05) reduction in serum bilirubin levels with silymarin and lycopene 10mg/kg treated groups signifying protection against hepatic damage, while vehicle control and lycopene 5mg/kg treated groups had high bilirubin values. Similarly, significant (p <0.001) reduction in the levels of serum transaminases were observed with all the treatment groups though more evident in the positive control and lycopene 10mg/kg treated groups. Conclusions: The results of the present study prove that lycopene exerts hepatoprotective effect against paracetamol and anti-tubercular drugs induced hepatic damage in rats. Lycopene needs to be evaluated in other models of hepatotoxicity and further studies are required to delineate its mechanism of action. Lycopene could be a potential hepatoprotective for clinical use in future.